Pengkayaan Tanah Bekas Tambang Emas dengan Penambahan Lumpur IPAM sebagai Media Pertumbuhan Sawi (Brassica juncea L.) - Gusrizal, Nuraini, Riza Linda (Universitas Tanjungpura, 2014)
Soil of former gold mine requires soil quality improvement through increasing organic matter compound that may be sourced from the sludge of water treatment plant (IPAM). IPAM sludge which a by-product of water treatment from Kapuas river contains humic substance. The research aimed to discover the effects of former gold mine soil improved by IPAM sludge addition on mustard (Brassica juncea L.) growth. The research was conducted from August to October 2013. The research used Completely Randomized Design which consists of five planting media combination with five replications following replacement series method. The planting media combinations used are : Treatment A (0 % IPAM sludge : 100% former gold mine soil), Treatment B (20 % IPAM sludge : 80% former gold mine soil), Treatment C (40 % IPAM sludge : 60% former gold mine soil), Treatment D (60 % IPAM sludge : 40% former gold mine soil) and Treatment E (80 % IPAM sludge : 20% former gold mine soil). The results showed that the combination of 60% IPAM sludge: 40% former gold mine soil media significantly affecting the growth parameters of mustard, which are: up to 397.80 cm2 leaves area growth, 35.12 g wet mass and 0.42 g dry mass.